Peran Produsen dalam Mengurangi Sampah Plastik - Zainuddin, Fuad (Program Studi Manajemen FEBM UMRAH, 2023)
Plastic waste is a type of waste that poses a serious risk to the environment because it tends to be produced in larger quantities and because plastic bags are a xenobiotic pollutant and are difficult to degrade through natural processes. Between 4.8 and 12.7 million metric tons of plastic are estimated to reach the oceans each year, according to the World Population Review. Indonesia is one of the 5 countries that throws the most rubbish into the sea according to the 2021 report. Based on information from the Ministry of Environment and Forestry (KLHK), overall there will be 68.5 million tons of waste produced nationally in 2021. In 2022, of which 11.6 million tons will be plastic waste. The amount of plastic waste has not decreased significantly due to the implementation of the paid Plastic Policy. Therefore, different strategies are needed to reduce plastic waste production. This research uses a qualitative method with a descriptive analytical approach. The aim of this study is to provide a broad overview of the steps the government can take to reduce the production of plastic waste. By focusing on reducing plastic use, the Manufacturer Waste Reduction Roadmap could be a means to minimize plastic waste, the study found. Encouraging the use of more environmentally friendly packaging must be accompanied by efforts to reduce plastic use. A different approach to reducing the amount of plastic waste in society is to determine the smallest possible packaging size.